Efficacy and implications of a 48-h cutoff for video capsule endoscopy application in overt obscure gastrointestinal bleeding - Kim, Seung Han; Keum, Bora; Chun, Hoon Jai; Yoo, In Kyung; Lee, Jae Min; Lee, Jong Soo; Nam, Seung Joo; Choi, Hyuk Soon; Kim, Eun Sun; Seo, Yeon Seok; Jeen, Yoon Tae; Lee, Hong Sik; Um, Soon Ho; Kim, Chang Duck (Endoscopy International Open, 2015)
Background and study aims: Early video capsule endoscopy (VCE) may provide a high diagnostic yield and improve clinical outcomes in patients with overt obscure gastrointestinal bleeding (OGIB); however, there is no practical recommendation for the ideal timing of VCE application in overt OGIB. Therefore, this study investigated the diagnostic yield and efficacy of VCE to assess overt OGIB with respect to the timing of application.Patients and methods: We retrospectively enrolled patients who had undergone VCE for overt OGIB between April 2004 and February 2014 at a tertiary referral academic center. We included hemodynamically stable patients who underwent VCE for overt OGIB after negative bidirectional endoscopy. We analyzed the diagnostic yield of VCE, therapeutic intervention rate, and length of hospital stay. Results: A total of 94 patients underwent VCE to assess overt OGIB. The diagnostic yields in the groups that underwent VCE < 48 h and > 48 h from the last overt OGIB were 66.7 % and 40.6 %, respectively (P = 0.019). Therapeutic intervention was performed in 26.7 % and 9.4 % of patients in the < 48-h and > 48-h groups, respectively (P = 0.028). The mean lengths of hospital stay in the < 48-h and > 48-h groups were 5 days (95 % confidence interval [CI], 4.8 – 7.7) and 7 days (95 %CI, 6.9 – 10.1), respectively (P = 0.039). Conclusions: Performing VCE within 2 days from the last overt OGIB results in a higher diagnostic yield, higher therapeutic intervention rate, and shorter hospital stay. Therefore, VCE application with a 48-h cutoff could improve the outcome of patients with overt OGIB.